Assessment of Culture/Preservation Conditions of Human Islets for Transplantation. (March 2022) - Shindo, Yoshitaro; Kalivarathan, Jagan; Saravanan, Prathab Balaji; Levy, Marlon F.; Kanak, Mazhar A.
Islet culture before clinical transplantation has been adopted by various centers, but its effect on the survival and function of islets relative to the culture conditions and media needs further assessment. Human islets were cultured or preserved under four different conditions and three media options. Parameters such as recovery, viability, function, islet damage, and gene expressions for markers of hypoxia, and inflammation were assessed after 48-h culture or preservation. Preservation of islets was performed at 4°C in Connaught's Medical Research Lab (CMRL) and University of Wisconsin (UW) media. Islets were cultured at 22°C, 37°C, and 37°C–22°C in CMRL and PRODO culture media. Islets preserved in UW solution had visually good morphology and exhibited higher recovery with less islet damage compared with the rest of the groups, whereas islets preserved in CMRL at 4°C resulted in poor morphology, recovery, viability, and function compared with the rest of the treatment conditions. Culture at 22°C and 37°C demonstrated an increase in the expression of inflammatory and hypoxia-related genes. In conclusion, islets preserved at 4°C in UW solution showed the best overall outcomes after 48 h compared with islets cultured at 22°C, 37°C, or 37°C–22°C in PRODO. Advancement in islet culture media is warranted to reduce inflammatory gene activation and improve recovery of islets for transplantation.